PRAGMATONYMS AND BRAND ELEMENTS REPRESENTING BRAND NAMES - Sabo Akhmadalieva Murodovna; Shavkatova Navruza Zoirjonovna (Galaxy International Interdisciplinary Research Journal, 2024)
The article talks about how today the brand names has become a broad concept that includes several elements.